Traditional Chinese medicine Zhusha Anshen Wan: protective effects on liver, kidney, and intestine of the individual drugs using 1H NMR metabolomics - Wang, Dalu; Yu, Chong; Liu, Beixing; Wang, Haifeng (Frontiers in Pharmacology, 2024)
In our study, we utilized a metabonomics approach based on high-resolution 1 H nuclear magnetic resonance spectroscopy to investigate the reduction of toxicity by each herb in Zhusha Anshen Wan (ZSASW). This study aimed to elucidate the metabolic mechanism involved in the detoxification of a single drug during compound prescription. Male Wistar rats were divided into six groups: the control group, the cinnabar group (treated with cinnabar), the CAS group (treated with cinnabar and Angelica sinensis), the CRG group (treated with cinnabar and Rehmannia glutinosa Libosch), the CCC group (treated with cinnabar and Coptis chinensis French), and the CGU group (treated with cinnabar and Glycyrrhiza uralensis Fisch). Partial least squares-discriminant analysis (PLS-DA) was conducted to distinct different metabolic profiles in the urine and serum from the rats. Liver and kidney histopathology examinations, as well as analysis of serum clinical chemistry analysis, were also carried out. The metabolic profiles of the urine and serum of the rats in the CGU and CCC groups were remarkably similar to those of the control group, while those of the CRG and CAS groups were close to those of the cinnabar  Corresponding author: Shenyang 110016, China.